Global Gay: The Next Frontier in Human Rights - Laine, Remi; Martel, Frédéric (France, 2014)
A global revolution is underway to obtain what the UN Secretary General Ban Ki Moon and Barack Obama call "the final frontier in human rights": the universal decriminalization of homosexuality. "Global gay" follows this battle for decriminalization of homosexuality through the lives and work of some of it fearless pioneers worldwide.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films